Gene editing: a promising tool to increase biodiversity in a sterile crop such as banana (3rd International Agrobiodiversity Congress, 20-22 May, 2025, Kunming, China) - Van Den Broeck, Senne; Ngapout, Yvan; Panis, Bart; Vanderschuren, Herve (2025)
Crop improvement through genome editing traditionally depends on the possibility to segregate out the editor T-DNA cassette after genome editing has occurred. The removal of the T-DNA cassette has two main benefits: it prevents further, often off-target editing and most importantly, facilitates regulatory approval. However, for vegetatively propagated and sterile crop species (such as Cavendish bananas), as well as those with long juvenility, transgene outcrossing is virtually impossible. Therefore, genome editing techniques are required that introduce desired edits immediately in the T0 generation without insertion of a transgene in the chromosomal DNA. Here, we present a novel method for transgene-free genome editing in sterile banana (Musa spp.) cultivar Williams, employing an Agrobacterium tumefaciens-mediated base editing approach. Editing of the acetolactate synthase (MaALS) genes in banana allowed effective selection of edited plants. Through a co-editing strategy, transgene-free plantlets with mutations at two target sites were regenerated. The presented method can be leveraged in the future to increase the resilience of both commercial and local banana cultivars against the current and future agricultural challenges, and is expected to comply with the most restrictive regulations on genome-edited crops.